The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1046/j.1365-2648.1993.18091443.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a better understanding of patients with irritable bowel syndrome

Abstract: This study was undertaken by sending a questionnaire to 148 people suffering from irritable bowel syndrome (IBS). The respondents all were members of the IBS Network, a national independent organization formed to help alleviate the suffering and distress of people diagnosed as having irritable bowel. They were asked about their symptoms, the medical tests they had undergone, how they felt about the treatment they received, and how IBS affected their lives. The study found that IBS affected all aspects of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 4 publications
2
65
0
1
Order By: Relevance
“…Studies have shown that irritable bowel syndrome can affect sleep, 1 employment, 2 sexual functioning, 3 leisure, travel, diet, and can cause depression and anxiety. 4,5 Questionnaires have been used in clinical research, as well as by physicians, to describe symptoms of patients with irritable bowel syndrome and to differentiate irritable bowel syndrome from organic conditions such as in¯ammatory bowel disease. 6,7 None of these questionnaires, however, have focused exclusively on measuring the impact of irritable bowel syndrome on dimensions of quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that irritable bowel syndrome can affect sleep, 1 employment, 2 sexual functioning, 3 leisure, travel, diet, and can cause depression and anxiety. 4,5 Questionnaires have been used in clinical research, as well as by physicians, to describe symptoms of patients with irritable bowel syndrome and to differentiate irritable bowel syndrome from organic conditions such as in¯ammatory bowel disease. 6,7 None of these questionnaires, however, have focused exclusively on measuring the impact of irritable bowel syndrome on dimensions of quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients with IBS are more likely to have symptoms of psychological distress, 1±7 use more health care, 8 and have reduced quality of life manifested by impact on sleep, 9 employment, 6 sexual functioning, 10 leisure, travel and diet. 11,12 While physicians have not yet agreed on a set of symptoms that de®ne IBS, they do recognize that the disease exists on a continuum. 13 Even patients, when asked to described their symptoms, categorize themselves in terms of severity of their IBS.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has found that patients with IBS have decreased sexual functioning, 38 higher rates of psychological symptoms 39±41 and problems with employment, travel, leisure and diet. 42 Some studies have examined general quality of life in patients with IBS. Using the Short-Form 36 (SF-36), a commonly used general quality of life questionnaire, O'Keefe et al 10 found that in a population of elderly people, those with IBS and frequent abdominal pain had lower scores compared with either those with other bowel disorders or a control group.…”
Section: Quality Of Lifementioning
confidence: 99%